2021
DOI: 10.1007/s00500-021-05904-0
|View full text |Cite
|
Sign up to set email alerts
|

Supplier’s cooperation strategy with two competing manufacturers under wholesale price discount contract considering technology investment

Abstract: Cooperation between upstream suppliers and downstream manufacturers in technology investment is a popular way to improve production technology for reducing suppliers' production costs of key components. Technology investments undertaken by manufacturers and wholesale price discount contract provided by suppliers have an important impact on their cooperation. This paper explores whether a supplier should cooperate with two downstream competing manufacturers to accept their technology investments to reduce the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Sarkar et al (2020b) suggested a price discount coordination mechanism in a two-level supply chain with price sensitive customer demand to encourage the supply chain players to take part in joint decision-making strategy. Yang et al (2021) explored the optimal cooperation strategy between an upstream supplier and two competing manufacturers considering a wholesale price contract and manufacturers' technology investment. In order to reduce products' carbon emissions.…”
Section: Price Discount Contractmentioning
confidence: 99%
“…Sarkar et al (2020b) suggested a price discount coordination mechanism in a two-level supply chain with price sensitive customer demand to encourage the supply chain players to take part in joint decision-making strategy. Yang et al (2021) explored the optimal cooperation strategy between an upstream supplier and two competing manufacturers considering a wholesale price contract and manufacturers' technology investment. In order to reduce products' carbon emissions.…”
Section: Price Discount Contractmentioning
confidence: 99%
“…On the contrary, when the supplier reduces the online sales price of the product, the sales volume of the supplier's online sales channel will be increased, and the wholesale price determined by the supplier will be reduced. To attract consumers, the retailer will also reduce the online and offline sales price of the product [ 5 , 30 , 31 ]. Therefore, the price discount contract will not cause the situation that there is only single-channel demand in the supply chain system.…”
Section: Construction Of the Dual-channel Supply Chain Model Based On...mentioning
confidence: 99%